Marvel : illustrated guide to the Spider-verse - Sumerak, Marc (Insight Editions, 2023)
"Take a tour through the colorful worlds of Marvel's Spider-Verse in this comprehensive guidebook detailing the lives of its many web-slingers. Follow Gwen Stacy--better known as Ghost-Spider--as she jumps between dimensions visiting the countless friendly (and some not-so-friendly) neighborhood Spider-folk whom she has met in her adventures across the Marvel Multiverse. From Peter Parker to Miles Morales, from Spider-Ham to Spider-Man 2099, more than 60 of Gwen's iconic wall-crawling colleagues are profiled here, each illustrated with amazing original art. Thrilling and vibrant, this arachnophile's treasury is a must-have collectible for every Spider-fan!"--Provided by publisher.